2016
DOI: 10.14238/pi50.1.2010.42-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of emotional and behavior problems in obese children using Child Behavior Checklist (CBCL) and 17-items Pediatric Symptom Checklist (PSC-17)

Abstract: Background Obesity can result in emotional and behavior problems in school-age children. Child Behavior Checklist (CBCL) is a standard instrument for evaluating behavior problems, however it is considered not practical. The 17-item Pediatric Symptom Checklist (PSC-17) is a more simple instrument but its diagnostic value has never been evaluated in obese children.Objectives To evaluate the diagnostic value of PSC-17 compared to CBCL as the gold standard.Methods This cross-sectional study was done in May - June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
(28 reference statements)
0
10
0
3
Order By: Relevance
“…This was lower compared to other studies in Indonesia, which showed positive prevalence of 22-29%. 5,8 This difference was predicted to be caused by different sample sizes and data retrieval method. The PSC-17 data collection in one study was done using verbal interviews to parents instead of self-filled.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was lower compared to other studies in Indonesia, which showed positive prevalence of 22-29%. 5,8 This difference was predicted to be caused by different sample sizes and data retrieval method. The PSC-17 data collection in one study was done using verbal interviews to parents instead of self-filled.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, attention sub-scale covers attention deficit-hyperactivity disorder, which is screened by following symptoms: "fidgety, unable to sit still", "daydreams too much", "has trouble concentrating", "acts as if driven by a motor", and "distracted easily". 5 Parents rated each item based on the frequency of "never", "sometimes", or "often". Their responses were then scored as 0, 1, or 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations